The Factors Effecting Economic Growth in TRNC - Alçıner, Rauf (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The main topic of this study is the qualitative and quantitative analysis of the economy of Cyprus throughout the historical process. The process between the Middle Ages and the British period was summarized. In the introduction, the natural relationship between the economy and humankind and the further extent of this relation was constituted within theorical context. Basically, in this study Cyrus Economy history has been seperated into 4 chapters in order of priorities and it has been studied in detail. The first chapter is a brief summary of Cyprus economy between 1878-1963 and before British period, the second chapter is the economy of Turkish Federated State of Cyprus between 1974-1983, the third chapter is the liberalisation of the economy of Turkish Republic of Northern Cyprus between 1983-2000, the fourth chapter is economic integration period of Turkish Republic of Northern Cyprus between 2000-2015 and in the fifth chapter, there was an attempt to associate the factors that affect economic growth with the related parameters with an empirical study by using regression model. The main framework of chapters 2,3 and 4 was prepared based on the following sub headings; general situation, international situation, sectoral distribution of the GDP, foreign trade and main economic indicators. These sub headings was chosen as the most critical parameters that affect the growth in Cyprus economy and the annual changes in parameters according to this prediction has been associated in the context of how it affected the local economy, politics and foreign policy. At the end of the study Regression model used to analyzed the GDP growth with related variables. Keywords: Gross domestic product, Productivity, Population, Trade

ÖZ : Bu çalışmanın temel konusu Kıbrıs’ın ekonomisinin tarihi süreç içerisinde nitel ve nicel olarak analiz edilmesidir. Ortaçağdan İngiliz dönemine kadar olan süreç özet şekilde oluşturulmuştur. Giriş bölümünde ekonominin insanoğlu ile doğal ilişkisi ve bu ilişkinin ileri boyutları teorik bağlamda oluşturulmuştur. Çalışmada temel olarak, Kıbrıs Ekonomisi tarihi, öneme göre 4 bölüme ayrılmış ve detaylı olarak incelenmiştir. Birinci bölüm İngiliz dönemi 1878-1963 ve İngiliz dönemi öncesinde Kıbrıs ekonomisinin kısa özeti, ikinci bölüm 1974-1983 Kıbrıs Türk Federe Devleti ekonomisi, üçüncü bölüm 1983-2000 Kuzey Kıbrıs Türk Cumhuriyeti ekonomisi liberalleşme dönemi, dördüncü bölüm 2000-2015 Kuzey Kıbrıs Türk Cumhuriyeti ekonomisi ekonomik entegrasyon dönemi ve son olarak beşinci bölümde ise regrasyon modeli kullanılarak ekonomik büyümeyi etkileyen faktörler ampirik bir çalışma ile ilgili parametrelerle ilişkilendirilmeye çalışılmıştır. 2,3 ve 4üncü bölümlerdeki ana çerçeve; genel durum, uluslararası durum, gayri safi hasılanın sektörlere göre dağılımı, dış ticaret ve temel ekonomik göstergeler alt başlıkları temel alınarak sıralanmıştır. Bu alt başlıklar Kıbrıs ekonomisindeki büyümeyi etkileyen en kritik parametreler olarak belirlenmiş ve bu öngörüye göre parametrelerde ki yıllık değişimler nitel ve nicel olarak, yerel ekonomi politikaları ve dış ülke politikaları ile nasıl etkilendiği bağlamında ilişkilendirilmiştir. Çalışmanın sonunda, regrasyon analizi modeli, GSYIH bağımlı değişken olarak ilgili bağımsız değişkenlerle model kurulup incelenmiştir. Anahtar kelimeler: Gayri safhi yurt ici hasıla, Üretkenlik, Nüfus, Ticaret
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Assoc. Prof. Dr. Şule Aker.
Keywords: Economic Conditions - Cyprus (Turkish Republic of Northern Cyprus, 1983-); Gross domestic product; Productivity; Population; Trade; Business Administration